1987
DOI: 10.1111/j.1365-2273.1987.tb00212.x
|View full text |Cite
|
Sign up to set email alerts
|

Discriminant analysis in predicting survival of patients with cancer of the larynx or hypopharynx

Abstract: In order to assess the feasibility of computer-assisted prognostication, step-wise discriminant analysis was applied to data retrospectively obtained from 243 patients who underwent surgery for cancer of the larynx. In all, 62 variables were studied in each patient. Ninety-four out of 243 patients had complete information on the 62 variables studied. With data from these 94 patients a linear discriminant function was obtained, with an overall accuracy of 87.2%. The rate of correct prediction was 84.6% for canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0
2

Year Published

1991
1991
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 13 publications
1
7
0
2
Order By: Relevance
“…Performance status and the development of a metachronous tumor were additional parameters correlated with the RR of death for absolute survival. Although limited by the retrospective nature of the study, the results presented here are in keeping with much of the data reported so far 7,9,10,12,17,27,28,32 and could well represent a valid starting point for new prospective confirmatory studies.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Performance status and the development of a metachronous tumor were additional parameters correlated with the RR of death for absolute survival. Although limited by the retrospective nature of the study, the results presented here are in keeping with much of the data reported so far 7,9,10,12,17,27,28,32 and could well represent a valid starting point for new prospective confirmatory studies.…”
Section: Discussionsupporting
confidence: 83%
“…46 The strong prognostic value of factors related to N status has been demonstrated by several multivariate analyses. 6,7,10,14,16,17,19,21,22,26,28,32,33 Although extracapsular spread has been unanimously found to have a significant impact on survival, 10,17,28,32,33 conflicting results have been obtained on the number of metastatic lymph nodes. 6,16,17,32,33 Similarly, the level of lymph node involvement was a significant predictor of outcome in a study by Moe et al, 33 whereas no prognostic relevance was reported for this variable by Kowalski et al 32 All the factors related to N status significantly affected survival in our univariate analysis, whereas only extracapsular spread was associated with a higher RR of death in the final multivariate model.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…T h e prognosis for patients with squamous cell carcinoma of the head and neck (HNSCC) is determined by patient factors (ie, age, sex, and status of performance), tumor factors (ie, site of primary tumor, tumor size, and possible metastatic spread), and treatment factors (ie, the response to surgery, radiotherapy, and chemotherapy). [1][2][3][4] Until now, the TNM classification system has been the most important determinant in estimating prognosis and therefore in deciding type of treatment, the rule being that large tumors with evidence of metastatic spread have worse prognosis as compared with small and locally restricted tumors. ',' There is, however, a wellknown difficulty to predict individual prognosis for cases of HNSCC, as patients and tumors in similar condition, comparably staged and treated, have extremely disparate clinical outc o m e~.~ Descriptive histopathologic morphology and biologic behavior has been correlated with prognosis in a histologic malignancy grading system introduced by Jakobsson et al 5 This system is based on 4 different morphologic characteristics for the tumor cell population and 4 characteristics for the tumor-host relationship.…”
mentioning
confidence: 99%